The topological degree method for equations of the Navier-Stokes type. (1997) - Dmitrienko, V. T.; Zvyagin, V. G.
Abstract : We obtain results of existence of weak solutions in the Hopf sense of the initial-boundary value problem for the generalized Navier-Stokes equations containing perturbations of retarded type. The degree theory for mapsA − g, whereA is invertible andg is𝒜 -condensing, is used.